Monsoon revolution republicans, sultans, and empires in Oman, 1965-1976 - Takriti, Abdel Razzaq (Oxford historical monographs, 2013)
The Dhufar revolution in Oman (1965-1975) was the longest-running major armed struggle in the history of the Arabian Peninsula, Britain's last classic colonial war in the region, and one of the highlights of the Cold War in the Middle East. Monsoon Revolution retrieves the political, social, and cultural history of that remarkable process.